Fusarium graminearum‐induced shoot elongation and root reduction in maize seedlings correlate with later seedling blight severity. (18th July 2018) - Zhou, Shaoqun; Bae, Justin S.; Bergstrom, Gary C.; Jander, Georg
Abstract: Fusarium graminearum seedling blight is a common disease of maize ( Zea mays ). Development of genetic resistance to seedling blight in maize germplasm requires efficient and accurate quantitative assessment of disease severity. Through artificial inoculation experiments under controlled growth conditions, we determined that host genotype, pathogen genotype, and infection dose influence the extent to which F. graminearum induces shoot elongation and inhibits root growth in maize seedlings. A comparison of 15 maize inbred lines showed independent variation of these two fungus‐induced effects on seedling growth. In a broader survey with nine commercial maize hybrids and three field‐collected fungal isolates, there was significant correlation between these seedling growth responses, as well as with later seedling blight severity. Analysis of variance suggested that this variation and the observed correlative relationships were primarily driven by differing pathogenicity of the three fungal isolates. Together, our results indicate that F. graminearum ‐induced shoot elongation and root reduction in maize seedlings have distinct underlying physiological mechanisms, and that early observations of seedling growth responses can serve as a proxy for investigating natural variation in host resistance and pathogen aggressiveness at later growth stages.